1988
DOI: 10.1007/bf00449677
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the intercondylar eminence in children and adolescents

Abstract: The treatment of choice of completely dislocated fractures of the intercondylar eminence is controversial. Recently, Zifko and Gaudernak [14] introduced a new classification in which they distinguish between two different types of intercondylar fractures: Type A: isolated avulsion of the anterior cruciate ligament Type B: fractures including the intercondylar eminence In order to assess whether this new classification could lead to a better selection of patients requiring open reduction, 19 children were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 8 publications
1
24
0
2
Order By: Relevance
“…Moreover, they support the opinion that the surgical option facilitates a more satisfactory reduction of the fracture, thus avoiding the possible risk of a meniscal entrapment under the fractured tibial eminence or a possible healing of the fracture in a non-anatomical position, with the consequence of further instability or loss of extension of the knee [4,6,13,19].…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, they support the opinion that the surgical option facilitates a more satisfactory reduction of the fracture, thus avoiding the possible risk of a meniscal entrapment under the fractured tibial eminence or a possible healing of the fracture in a non-anatomical position, with the consequence of further instability or loss of extension of the knee [4,6,13,19].…”
Section: Discussionsupporting
confidence: 52%
“…Several older studies have proposed that type II, III and IV fractures do not require fixation [3, 11, 23, 24]. Table 4 outlines differences in management of these fractures patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 outlines differences in management of these fractures patterns. Several papers have reported worse results for type III fractures treated non-operatively [3, 14, 30, 32]. A retrospective case study of 61 paediatric patients found a direct correlation between fracture displacement after healing and knee laxity ( r  = 0.74, p  < 0.001) [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation is because of an increase in the local blood supply during the healing stage [29]. This modification is usually asymptomatic and is not associated with knee flexion [25,30], because of the median situation of the callus [5]. The curettage of the fracture area before internal fixation, in our experience, allowed elimination of the variation of the shape and size of the tibial intercondylar eminence.…”
Section: Discussionmentioning
confidence: 95%